De novo designed proteins: a breakthrough in snakebite treatment - Vazquez Torres, Susana (Henry Stewart Talks, 2026)
De novo protein design, Snakebite envenoming & antivenom development, Computational protein engineering, Deep learning tools, In vitro and in vivo validation, Global health and democratization of drug discovery